Structural and microstructural analyses on Sm-modified BaTiO3 obtained from the Pechini's method - Oliveira, M. A. [UNESP]; Mendez-Gonzalez, Y.; M'peko, J. C.; Hernandes, A. C.; Guo, R.; Bhalla, A. S.; Guerra, J. D. S. (Taylor & Francis Ltd, 2018)
Barium titanate (BaTiO3) ceramics, prepared by the Pechini's method, were investigated considering the influence of the samarium-modifier concentration. Nanosized crystallites in the order of 15-20nm have been successfully obtained by this synthesis process. The structural properties analyzed from the X-ray diffraction technique, confirmed a single ferroelectric phase with no additional secondary-phases, and suggest the amphoteric character (A- or B-site occupancy) of the Sm3+ ion into the BaTiO3 structure. This effect, which has not been previously reported, has been also confirmed from microstructural (scanning electron microscopy) analysis. The obtained results reveal to be the starting point for further detailed investigations of the real amphoteric behavior of the Sm3+ ion, and other rare-earth elements in perovskite-type structure systems.
Keywords: Pechini's method; nano-powders; BaTiO3